On slow reading and slow violence: slow reading to recognise and address violence done to nature - Bruce, Robin (The Stellenbosch Socratic Journal, 2024)
Could reading about nature in a different way aid us in recognising and addressing the damage humans are doing to it? In this paper, I argue that Michelle Boulous Walker’s theory of slow reading can help us recognise and address climate change, radiological violence, deforestation, and other slow violences done to nature. Reading slowly, and taking one’s time to dwell is an open, understanding, and embodied concept, one that values returning, again and again, to uncover anew the wisdom that lies within a text. Slow violence, conceptualised by Rob Nixon, is a pervasive and seemingly uneventful violence, where its effects are temporally and spatially removed from its cause. With slowness being a common factor between these concepts, I argue that one must first slow down to recognise slow violence. I will defend this view by discussing three aspects of slow reading and analysing how those three aspects connect to slow violence and aid in recognising and addressing slow violence. These three aspects of slow reading are openness, understanding, and embodiment. Through these aspects, slow reading not only aids in recognising slow violence, but it also aids in holding space for the other, therefore holding a twofold approach; both recognising and addressing slow violence.